Using Argo Floats to Characterize Altimetry Products: A Study of Eddy-Induced Subsurface Oxygen Anomalies in the Black Sea - Capet, Arthur; Taburet, Guillaume; Mason, Evan; Pujol, Marie Isabelle; Grégoire, Marilaure; Rio, Marie-Hélène (Frontiers in Marine Science, 2022)
The identification of mesoscale eddies from remote sensing altimetry is often used as a first step for downstream analyses of surface or subsurface auxiliary data sets, in a so-called composite analysis framework. This framework aims at characterizing the mean perturbations induced by eddies on oceanic variables, by merging the local anomalies of multiple data instances according to their relative position to eddies. Here, we evaluate different altimetry data sets derived for the Black Sea and compare their adequacy to characterize subsurface oxygen and salinity signatures induced by cyclonic and anticyclonic eddies. In particular, we propose that the theoretical consistency and estimated error of the reconstructed mean anomaly may serve to qualify the accuracy of gridded altimetry products and that BGC-Argo data provide a strong asset in that regard. The most recent of these data sets, prepared with a coastal concern in the frame of the ESA EO4SIBS project, provides statistics of eddy properties that, in comparison with earlier products, are closer to model simulations, in particular for coastal anticyclones. More importantly, the subsurface signature of eddies reconstructed from BGC-Argo floats data is more consistent when the EO4SIBS data set is used to relocate the profiles into an eddy-centric coordinate system. Besides, we reveal intense subsurface oxygen anomalies which stress the importance of mesoscale contribution to Black Sea oxygen dynamics and support the hypothesis that this contribution extends beyond transport and involves net biogeochemical processes.